Industrial Training Report: Shared Facilities Library of Pagoh Education Hub / Muhammad Shakirin Idris - Idris, Muhammad Shakirin
This paper was produced to fulfill the requirement of a course named IMC 690, Industrial Training which compulsory course was for students before finishing their Bachelor of Science in Information Studies (Hons.) Library Management. This paper reports the task that had been done, activities, special project and lesson learned during 5-months internship at Shared Facilities Library of Pagoh Education Hub There are also background, services, facilities and collection of at Shared Facilities Library of Pagoh Education Hub that included in this report. Based on the industrial training, some limitations and recommendations have been proposed in order to help the organization to improve its services for the upcoming years. In this report, readers can take a look at all the activities have been done during the industrial training and it can give an overview to future students that will be taking this course.